A mathematical model of parathyroid gland biology. Issue 7 (29th March 2019) - Schappacher‐Tilp, Gudrun; Cherif, Alhaji; Fuertinger, Doris H.; Bushinsky, David; Kotanko, Peter
Abstract: Altered parathyroid gland biology in patients with chronic kidney disease (CKD) is a major contributor to chronic kidney disease‐mineral bone disorder (CKD‐MBD). This disorder is associated with an increased risk of bone disorders, vascular calcification, and cardiovascular events. Parathyroid hormone (PTH) secretion is primarily regulated by the ionized calcium concentration as well as the phosphate concentration in the extracellular fluid and vitamin D. The metabolic disturbances in patients with CKD lead to alterations in the parathyroid gland biology. A hallmark of CKD is secondary hyperparathyroidism, characterized by an increased production and release of PTH, reduced expression of calcium‐sensing and vitamin D receptors on the surface of parathyroid cells, and hyperplasia and hypertrophy of these cells. These alterations happen on different timescales and influence each other, thereby triggering a cascade of negative and positive feedback loops in a highly complex manner. Due to this complexity, mathematical models are a useful tool to break down the patterns of the multidimensional cascade of processes enabling the detailed study of subsystems. Here, we introduce a comprehensive mathematical model that includes the major adaptive mechanisms governing the production, secretion, and degradation of PTH in patients with CKD on hemodialysis. Combined with models for medications targeting the parathyroid gland, it provides a ready‐to‐use tool to explore treatment strategies. While the model is of particular interest for use in hemodialysis patients with secondary hyperparathyroidism, it has the potential to be applicable to other clinical scenarios such as primary hyperparathyroidism or hypo‐ and hypercalcemia. Abstract : We built a model of the parathyroid gland biology in hemodialysis patients based on the regulation of the calcium‐sensing receptor. The model spans several timescales, from the fast release of parathyroid hormone in the case of induced hypocalcemia to the development of cell hyperplasia in the case of reduced phosphate clearance and impaired vitamin D metabolism. The model provides a ready‐to‐use tool to analyze the complex system underlying secondary hyperparathyroidism.